Diurnal variation in the physiological responses of yaks - KRISHNAN, G; RAMESHA, K P; CHAKRAVARTY, P; CHOUHAN, V S; JAYAKUMAR, S (The Indian Journal of Animal Sciences, 2011)
The present study was carried out at National Research Centre on Yak. Healthy yaks (30) were divided into 3 groups, viz. calves, adult bulls and lactating yak cows. They were maintained under semi range system of management. The primary physiological responses were recorded at 4h intervals at alternate months throughout the year in all the 3 groups of yak. The physiological responses were minimum in the early morning and maximum during late afternoon. The physiological responses of calves were significantly (P<0.05) higher than adult bulls and lactating yak cows during late afternoon. In all the three groups of yak the physiological responses were significantly higher (P<0.05) during summer than winter. Â